Reference Equations for the Six-Minute Walk Test in Healthy Adults in Southwestern Colombia: a Cross-Sectional Study - Esther Cecilia Wilches-Luna; Hamilton Elías Rosero-Carvajal; Álvaro Javier Arias Balanta; Diana Marcela Quintero Medina; Mauricio Hernández-Carrillo; Jhonatan Betancourt Peña (Revista de Investigación e Innovación en Ciencias de la Salud)
Introduction. The six-minute walk test (6MWT) is a submaximal test to assess functional capacity for exercise. In Colombia, the distance of the 6MWT is compared with those predicted by reference equations from other countries. Besides, pedometric measurements have not been included in the test.